Budaya Populer sebagai Medium Perlawanan dan Penghindaran: Studi Kasus Situs Kaskus - Adrianto, Aditya Eko (PANTUN: Jurnal Ilmiah Seni Budaya, 2016)
The purpose of this study is to show how popular culture is formed and its influences ot he com-munity in the digital age. The data collected from Kaskus is analyzed to show how popular culture can become a medium of resistance and evasion against the dominant culture. Furthermore, throughout its development, Kaskus transformed from a social networking website into information/news website. Analyzed from kitsch standpoint, Kaskus is also actively using its potential to earn profit from its popularity in the community. Thus, using Cultural Capital and Field concepts popularized by Pierre Bourdieu, Kaskus, as a popular culture, can be analyzed thoroughly.Keyword: Popular Culture, kaskus, kitsch, resistance, evasion.